DEVELOPING INSTRUCTIONAL MEDIA APPLICATION OF WEBLOG TO IMPROVE THE STUDENT'S ABILITY IN WRITING DESCRIPTIVE TEXT AT SMP HKBP SIDORAME - Naomi Glory Novelia Manurung; Fenty Debora Napitupulu; Febrika Dwi Lestari Lumbantoruan (Program Studi Pendidikan Bahasa Inggris, 2024)
This study found the Developing Instructional Media Application Weblog To Improve The Student Ability In Writing Of Descriptive Text Smp VIII HKBP SIDORAME MEDAN. The objectives of this research are to know use the weblog application to improve students’ ability to write descriptive text. This research was designed for classroom action research by employing planning, action, observation, and reflection. The data is collected by giving tests to 20 students. The result showed that the application weblog can improve the ability to write descriptive text. Proven by the increase of the score from the mean score in pre-test cycle 1 mean = 51.00, post-test cycle 1 mean = 71.35 and cycle 2 pre-test mean = 52.83, post-test cycle 2 mean = 80.00.